IMPACT OF INTRA-ROW SPACING ON GROWTH AND YIELD OF SOME MAIZE CULTIVARS - Khan, Muhammad Bismillah; Asif, Muhammad; Aman, Madiha; Ahmad, Tauqeer (Journal of Research (Science), 2002)
Response of four maize cultivars namely Agaiti-85, Akbar, Golden and Platinum to different planting densities of 15,20, and 25 cm was studied under field conditions during Kharif 2001 at Multan. Platinum and Agaity-85 produced greater number of grains cob-1 and 1000-grain weight and thus resulted in higher grain yield as compared to other cultivars included in this study. These cultivars also gave highest leaf area index and higher biological yield than Akbar and Golden. Yield and yield components were also influenced significantly by different seeding density levels. Maximum grain yield was recorded at 20 cm planting density level, while the leaf area index and grains cob-1 were greater at 25 and 20 cm planting density level while 1000 grain weight was greater in 25 and 20 cm level and lowest at 15 cm level.